Sex, love & romance in the mass media : analysis & criticism of unrealistic portrayals & their influence - Galician, Mary-Lou (LEA's communication series., 2004)
This research-based text offers both foundational theories and practical applications of analysis and criticism of mass-media portrayals of sex, love and romance in a wide variety of mass media, from entertainment to advertising to news.